(untitled) (Qualitative Research Journal for Social Studies, 2026)
Owing the unique properties of absorption of sound, individual as well as composites of fiberglass- foam and minerals- fibers are used from a long time. However, there are some health hazards due to the conventional materials. To avoid these issue textile fiber materials can be a good alternative to be the traditional materials. Although the fiber materials made up textile are comparatively low absorber of sound but still they are a potential candidate as they are not harmful human being as well as to environment. To their eco-friendly nature these textile materials can be modified physically or chemically to enhance the sound proof properties. For the physical modification one can choose Nano-fibers, hollow fibers, bio component fibers, micro fibers and aerogel treated fibers which in-hand chemically treated fibers can be obtained via plasma and alkali treatment. The main theme to modify these structures is to dissipate the sound Energy. To achieve the sound, proof quality enhances surface area, increased roughness and tortuosity plays a vital role, the article reviews critically the methods of modifications used by many researchers, to enhance the sound absorption characteristics of textile fibers along with the efficiency of these techniques. The sound absorption coefficient of naturally present fibers can be increased up to 0.9 in mid and high frequencies by using alkali treatment method, whereas the value of this coefficient become pretty higher from micro, hollow and bio component fibers than the natural fibers.